Sel Punca sebagai Transformasi Alternatif Terapi - Widowati, Wahyu; Widyanto, Rahma Micho (Zenit, 2013)
Stem cells are cells that became the beginning of the growth  to others cell that constract the whole body of organisms, including human. Stem cells are from embryonic, fetal, or adult cells, which are capable to proliferate to cells in a long time, which this cell doesn’t have specific function, stem cells are able to differentiate  into specific cell that build tissues and organ systems. Stem cells have charateristic including :  undifferentiated cells, this cell is self-renewal, cells can differentiate into more than one type of cells (multipotent/pluripotent). Types of stem cells include embryonic stem cells derived from embryo, or inner cell mass (ICM) and adult stem cells found in bone marrow, cord blood, umbilical cord, peripheral blood, liver, skin, brain, dental pulp, fatty tissue. The uniqueness of stem cells give new hope as an alternative therapy or cells therapy for various types especially degenerative diseases. Keywords: stem cell, cell therapy